Konseling Kelompok Sebagai Sarana untuk Menyusun Strategi Karir yang Efektif - Okti Pravitasari; Adinda Dwi Cahyani; Latiffa Amanda Putri Nur; Innaya Aulia Putri; Ratna Sari Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines how effective group counseling is in improving career maturity and decision-making of students and college students. Approaches such as Trait and Factor, CBT, and CIP as well as creative media such as career bags and IT support the service. The method used was a literature review. The purpose of this study is to determine and analyze how effective group counseling services are in improving career readiness and maturity, as well as to determine its effect on learners' self-efficacy, decision-making, and problem-solving skills. The results showed that group counseling improved participants' career maturity, self-efficacy, and future planning, with a significant increase from pretest to posttest. The use of media and technology encouraged creativity and effectiveness of the services, although privacy and ethical issues still need to be addressed, especially for online services. In addition, external elements such as family and social environment influence. Therefore, group counseling-if conducted in a planned, flexible, sustainable, and appropriately evaluated manner-helps participants prepare for their careers.